2013
DOI: 10.1111/acem.12269
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital Research in Sub‐Saharan Africa: Establishing Research Tenets

Abstract: Prehospital care constitutes an important link in the continuum of emergency care and confers a survival benefit to injured and ill persons. As development of acute and emergency care in sub-Saharan Africa expands, there is a strong need to improve the delivery of prehospital care to help relieve the overwhelming regional morbidity and mortality attributable to time-sensitive, life-threatening conditions. Effective research is integral to prehospital care development, as it helps quantify the need for prehospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 18 publications
(40 reference statements)
2
41
0
Order By: Relevance
“…The majority of studies in HICs have shown that prehospital interventions for TBI patients to be life-saving (Alspaugh et al, 2000;Bernard et al, 2010;Lendrum, Kotze, Lockey, & Weaver, 2013;N. K. Mould-Millman, Sasser, & Wallis, 2013;Rudehill et al, 2002).…”
Section: Prehospital Trauma Care Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of studies in HICs have shown that prehospital interventions for TBI patients to be life-saving (Alspaugh et al, 2000;Bernard et al, 2010;Lendrum, Kotze, Lockey, & Weaver, 2013;N. K. Mould-Millman, Sasser, & Wallis, 2013;Rudehill et al, 2002).…”
Section: Prehospital Trauma Care Systemsmentioning
confidence: 99%
“…In researching prehospital trauma systems Mould-Millman et al provide tenets for best practice, including delineating prehospital care research priorities well in the context of the full continuum of trauma care since it is just one link in the chain of survival (N. K. Mould-Millman et al, 2013). A study in Tanzania has shown that trauma resulting from RTIs is a leading cause of intensive care utilization and differences in survival is linked to poor pre-hospital care and lack of EMS (Chalya et al, 2011).…”
Section: Traumatic Brain Injury In Low and Middle Income Countriesmentioning
confidence: 99%
See 1 more Smart Citation
“…8 The extent to which the formal and the informal transport system contribute to morbidity and mortality remain unknown. 6,10,11 In the Ashanti Region, patients requiring emergency inter-facility referrals are predominantly transported to a modern, 100 bed, National Accident and Emergency Center (AEC) at Komfo Anokye Teaching Hospital (KATH), in the regional capital, Kumasi. Built in 2008, the KATH AEC is home to the first emergency medicine (EM) residency training program in Ghana.…”
Section: Introductionmentioning
confidence: 99%
“…This ideally triggers a cascade of events resulting in a timely response of expertise, resources, and service directed to patient stabilization and/or safe emergency patient transportation to the nearest appropriate facility (1,6,7) . (4,8,9) . This reflected the efforts of pioneering physicians around the world who independently realized the need for a specialist in emergencies who would be available to patients at all times or day or night.…”
Section: Introductionmentioning
confidence: 99%